Education as a Tool for the Management of Poverty Alleviation Programme in Nigeria - Dare, M. O. (International Journal of Educational Management, 2022)
Education has unquestionably viewed as immunization ignorance, disease and poverty. On the basis of the above exposition, this paper examined the concept of education, types and functions which education performs in the society. Furthermore, the paper also examined the concept of poverty, causes of poverty and the various efforts made by the Federal Government of Nigeria towards poverty reduction. The paper also examined some related empirical studies on poverty and provided the rate of poverty in some African countries. In addition, the paper advanced various suggestions that could serve as antidotes to poverty alleviation in Nigeria. The paper proposed poverty reduction model that can enable education to perform its expected functions.